Assassins [videorecording (DVD)] - Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Helgeland, Brian; Stallone, Sylvester; Banderas, Antonio; Moore, Julianne; Mancina, Mark (Warner Home Video, 2010)
An info-highway thief is swept into a battle between two hitmen, in a world where what counts is not who makes the first move, but who survives the last.